The paradoxical effects of professional stereotypes on the quality of care by interprofessional teams: The contingent effects of team faultlines, team stereotypes, and championship behaviors - Sheffer Hilel, Galia; Drach-Zahavy, Anat; Endevelt, Ronit (Frontiers in Psychology, 2023)
Despite calls to ensure quality care via interprofessional teamwork, interprofessional teams do not necessarily perform effectively. This study focused on professional stereotypes emerging in interprofessional teams and examined the contingency effects of interprofessional team’s faultlines, professional stereotypes, and leader’s championship behaviors. The model was tested with a nested sample of 59 interprofessional teams, caring for five to seven residents they each cared for. Data collection employed a multisource (interprofessional team members), multimethod (validated questionnaires and data from residents’ medical files) strategy. The results indicated that faultlines are not directly harmful to team’s quality of care; instead, they are likely to impact quality of care only when team stereotypes emerge. Furthermore, whereas teams typified by high professional stereotypes require person-oriented championship leadership, for teams typified by low team stereotypes, championship leadership harms the quality of care they provide. These findings have implications for handling interprofessional teams. Practically, leaders must be well-educated to better analyse team members' needs and maintain the appropriate leadership style.